Maintenance Treatment With Low-Dose Decitabine After Allogeneic Hematopoietic Cell Transplantation in Patients With Adult Acute Lymphoblastic Leukemia - Liu, Jia; Jiang, Zhong-Xing; Xie, Xin-Sheng; Wan, Ding-Ming; Cao, Wei-Jie; Wang, Meng; Liu, Zhen-Zhen; Dong, Zhen-Kun; Wang, Hai-Qiong; Lu, Run-Qing; Zhang, Yin-Yin; Cheng, Qian-Qian; et al. (Frontiers in Oncology, 2021)
Background Post-transplant relapse remains a principal leading cause of failure after allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with adult acute lymphoblastic leukemia (ALL). The aim of this study was to investigate the efficacy and safety of low-dose decitabine on the prevention of adult ALL relapse after allo-HSCT. Methods In this prospective study, we enrolled 34 patients with ALL who underwent allo-HSCT from August 2016 to April 2020 and received low-dose decitabine maintenance treatment after transplantation. The primary objectives were cumulative incidence of relapse rate (CIR), overall survival (OS), and disease-free survival (DFS). The secondary objectives were graft-versus-host disease (GVHD) and safety. Results Among the enrolled 34 patients, 6 patients relapsed and 6 patients died. The 2-year CIR, OS, and DFS were 20.2, 77.5, and 73.6%, respectively. Subgroup analysis revealed the 2-year CIR, OS, and DFS rates of 12 patients with T-ALL/lymphoblastic lymphoma (LBL) were 8.3, 90, and 81.5%, respectively. None of the seven patients with T-ALL relapsed. During maintenance treatment, only one patient (2.9%) developed grade IV acute GVHD and four (11.8%) patients had severe chronic GVHD. Thirty-two patients (94.1%) developed only grade I to II myelosuppression, and two patients (5.8%) developed grade III to IV granulocytopenia. Conclusions Maintenance treatment with low-dose decitabine after allo-HSCT may be used as a therapeutic option to reduce relapse in patients with adult ALL, especially in patients with T-ALL. Our findings require confirmation in larger-scale controlled trials. Clinical Trial Registration Chinese Clinical Trials Registry, identifier ChiCTR1800014888.